Odsev razvoja bibliotekarske in informacijske znanosti na objave revije Knjižnica v obdobju 2012-2015 - Kavčič-Čolić, Alenka (Knjižnica, 2015)
The journal Knjižnica (Library) is the most important medium of scientific and professional communication in library and information science in Slovenia. As it is the only scientific journal in the field, it also reflects the evolving of library science in the country. The article focuses on the editorial board policy in the period of 2012 - 2015 in the context of prior research and bibliometric analyses of articles published in the journal. Statistical data and overviews outlining core themes and changes in professional and scientific publishing are given followed by a survey of most frequent themes in the last five years, resulting from development trends in the field. The recent development of information and communication technology led to new directions in library science, it caused significant changes in the profession and developed new tools and services. Consequently, the changes in the profession were reflected in the journal content and format. The findings on the state and development of Knjižnica from its beginnings up to the present time arise many questions about further directions of the journal.
Keywords: Knjižnica (periodična publikacija); the journal Knjižnica; scientific publishing; znanstveno publiciranje; library science; scientific development; bibliotekarstvo; informacijska znanost; the period 2012-2015; 2012/2015